The Effect of Tax Avoidance and Dividend Policies on Company Value With Leverage as Moderation Variables - Saragih, Muhammad Rizal; Rusdi, Rusdi (EAJ (Economic and Accounting Journal), 2021)
A high increase in company value is a long-term goal that must be achieved by a company, which is reflected in the market price of its shares because investors' assessment of the company can be seen through the movement of the stock prices of companies listed on the stock exchange. stock exchange for companies that have gone public. This has an impact on shareholders to maintain their investment and potential investors are interested in investing in the company. This study aims to analyze the effect of tax avoidance and dividend policy on firm value with leverage as a moderating variable. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018, totaling 166 companies, while the sample of this study was 18 companies with a purposive sampling method. The research method used is descriptive statistics, classic assumption testing and hypothesis testing multiple linear regression analysis. The results show that tax avoidance is not significant to firm value, dividend policy has a significant effect on firm value, leverage does not moderate tax avoidance on firm value, leverage. does not moderate dividend policy on firm value, and tax avoidance and dividend policy affect firm value